Вплив поліморфізма rs1137101 гена рецептора лептина на розвиток цукрового діабету 2 типу та ожиріння у таких хворих = Influence of polymorphism rs1137101 of the leptin receptor gene on diabetes mellitus 2 types development - Ziablitsev, S. V.; Pankiv, V. I.; Yuzvenko, T. Y. (Journal of Education, Health and Sport, 2016)
Ziablitsev S. V., Pankiv V. I., Yuzvenko T. Y. Вплив поліморфізма rs1137101 гена рецептора лептина на розвиток цукрового діабету 2 типу та ожиріння у таких хворих = Influence of polymorphism rs1137101 of the leptin receptor gene on diabetes mellitus 2 types development. Journal of Education, Health and Sport. 2016;6(4):503-514. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61750 http://ojs.ukw.edu.pl/index.php/johs/article/view/3844 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 28.04.2016. ВПЛИВ ПОЛІМОРФІЗМА rs1137101 ГЕНА РЕЦЕПТОРА ЛЕПТИНА НА РОЗВИТОК ЦУКРОВОГО ДІАБЕТУ 2 ТИПУ ТА ОЖИРІННЯ У ТАКИХ ХВОРИХ С. В. Зябліцев, В. І. Паньків, Т. Ю. Юзвенко Український науково-практичний центр ендокринної хірургії, трансплантації ендокринних органів і тканин МОЗ України, м. Київ Реферат Метою даного дослідження було вивчення ролі поліморфізму rs1137101 гена LEPR у розвитку цукрового діабету 2 типу і його впливу на клініко-лабораторні показники, пов'язані з ожирінням у цих хворих. Досліджено 103 пацієнта з діагнозом ЦД2, які мали клінічно виражені ускладнення. Контрольну групи склали 100 практично здорових осіб у відповідному віці. Аналіз поліморфних ДНК-локусів здійснювали методом полімеразної ланцюгової реакції у реальному часі (TaqMan® SNP Genotyping Assay). Результати показали, що алельний поліморфізм rs1137101 (223Gln>Arg) був асоційований з розвитком цукрового діабету 2 типу: алель Gln підвищує, а алель Arg – знижує (OR=1,55; p=0,030) ризик його розвитку. Наявність алелі G у хворих з діабетом сприяє розвитку ожиріння та його проявів, а саме – більш високим значенням маси тіла та індексу маси тіла, а також більшому рівню у крові лептину, тригліцеридів та ліпопротеїдів низкої щільності на тлі зменшення вмісту ліпопротеїдів високої щільності. Ризик розвитку ожиріння у таких хворих підвищено у 2,8 разив. Ключові слова: цукровий діабет 2 типу, ген рецептору лептину, rs1137101 ВЛИЯНИЕ ПОЛИМОРФИЗМА rs1137101 ГЕНА РЕЦЕПТОРА ЛЕПТИНА НА РАЗВИТИЕ САХАРНОГО ДИАБЕТА 2 ТИПА С. В. Зяблицев, В. И. Панькив, Т. Ю. Юзвенко Украинский научно-практический центр эндокринной хирургии, трансплантации эндокринных органов и тканей МЗ Украины, Киев Реферат Целью данного исследования было изучение роли полиморфизма rs1137101 гена LEPR в развитии сахарного диабета 2 типа и его влияния на клинико-лабораторные показатели, связанные с ожирением у этих больных. Обследовано 103 пациента, которые имели клинически выраженные осложнения. Контрольную группу составили 100 практически здоровых человек соответствующего возраста. Анализ полиморфных ДНК-локусов осуществляли методом полимеразной цепной реакции в реальном времени (TaqMan® SNP Genotyping Assay). Результаты показали, что аллельный полиморфизм rs1137101 (223Gln>Arg) был ассоциирован с развитием сахарного диабета 2 типа: аллель Gln повышает, а аллель Arg – снижает (OR=1,55; p=0,030) риск его развития. Наличие аллели Gln у больных с диабетом способствует развитию ожирения и его проявлений, а именно – более высоким значениям массы тела и индекса массы тела, а также большему уровню в крови лептина, триглицеридов и липопротеидов низкой плотности на фоне уменьшения содержания липопротеидов высокой плотности. Риск развития ожирения у этих больных повышен в 2,8 раза. Ключевые слова: сахарный диабет 2 типа, ген рецептора лептина, rs1137101 INFLUENCE OF POLYMORPHISM rs1137101 OF THE LEPTIN RECEPTOR GENE ON DIABETES MELLITUS 2 TYPES DEVELOPMENT S. V. Ziablitsev, V. I. Pankiv, T. Y. Yuzvenko Ukrainian Scientific-Practical Center of Endocrine Surgery, Transplantation of endocrine organs and tissues of the Ministry of Health of Ukraine, Kiev Abstract The aim of this research was a study of gene LEPR polymorphism rs1137101 role in diabetes mellitus 2 type development and his influences on the clinical and laboratory data, related to obesity for these patients. 103 patients are inspected, that had the clinically expressed complications. A control group was made by 100 practically healthy persons of corresponding age. The analysis of polymorphic DNA-loci was carried out by the method of polymerase chain reaction in real time (TaqMan® SNP Genotyping Assay). Results showed that allelic polymorphism of rs1137101 (223Gln>Arg) had been associated with diabetes mellitus 2 types development: allele Gln promotes, while allele Arg – reduces (OR=1,55; p=0,030) the risk of its development. Presence allele Gln for diabetic patients assists development of obesity and his displays, namely – to the higher values of weight, body mass index and also to the greater leptin, triglycerides and low-density lipoproteides blood levels on a background reduction of high-density lipoproteides maintenance. The obesity risk for these patients was increased in 2,8 times. Keywords: diabetes mellitus 2 types, leptin receptor gene, rs1137101